A Case Report of Neuroendocrine Tumor in Presacral Region: How Can It Be Managed? Laparoscopy versus Laparotomy - Behnaz Nouri; Hanieh Najafiarab; Shaghayegh Hooshmand Chayijan (International Journal of Fertility and Sterility, 2024)
Presacral or retrorectal tumors are rare, usually asymptomatic, and diagnosed accidentally during physical examinationor imaging. Symptomatic tumors may present with perianal pain, bowel dysfunction, and urinary symptoms dueto the mass compression or invasion of the surrounding tissues and organs. Surgical resection is the first choice fortreating presacral tumors. Clinicians should choose surgical procedures based on the location and size of the tumors.We presented a 43-year-old woman who suffered from pelvic pain and primary infertility from two years ago. A largemass between the posterior vaginal wall and the rectum was found on recto-vaginal examination. Magnetic resonanceimaging (MRI) revealed a large 120×115 mm benign multiloculated cystic mass. Eventually, the mass was removedthrough laparoscopic surgery. The pathology report indicated a carcinoid tumor (grade I) with no lymphovascularinvasion. Thus, presacral tumors are resectable through laparoscopy with lower complications than open surgery.